ANALISIS EFEKTIVITAS UNIT KOLAM AERASI BERDASARKAN ASPEK TEKNIS PADA INSTALASI PENGOLAHAN AIR LIMBAH SUWUNG DENPASAR - Wulantari, Sagung Anggun Istri; Widiantara, I Kadek; Wahyu Wijaya, I Made (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2025)
The government has built a Wastewater Treatment Plant (WWTP) to reduce environmental pollution. Suwung WWTP is a liquid waste treatment unit constructed using an aerated lagoon and sedimentation pond system to treat household wastewater in the areas around Denpasar, Sanur, and Kuta. The purpose of this study is to understand the technical design of the aerated lagoon unit at Suwung WWTP in Denpasar. This study uses a comparison of aerated lagoon design criteria with existing data from the aerated lagoon at Suwung WWTP. The study results on the quality of influent and effluent from the aeration ponds at Suwung WWTP have met quality standards according to the Bali Governor Regulation Number 16 of 2016 regarding BOD, TSS, pH, and DO parameters. The effectiveness of BOD removal in aerated lagoon I was 34.04% and in aerated lagoon II was 24.68%, while the TSS removal in aerated lagoon I was 23.72% and in aerated lagoon II was 11.68%. The existing aerated lagoon design complies with the design criteria indicators for aerobic flow through as per Annex II of PUPR Regulation No. 04 of 2017.